Stopy zwrotu z akcji sprzedawanych w dniu debiutu spółki na giełdzie - Czekaj, Karolina (Returns on WSE IPOs during the years 1996-2005, 2006)
The underpricing of IPOs has been a subject of theoretical and empirical investigations for decades. This article surveys the Polish market for initial public offerings (IPOs). The results of high first day returns are consistent with the international findings. The literature on IPOs offers a wide variety of explanations of this puzzle, which are summarized in this paper. This study also examines the relations between initial public offerings’ returns and the capital market conditions, confirming high correlation between them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 50-60